The Unique Case of Treasury Regulations Issued to Prevent Abuse - Olsen, Jonathan (Columbia Journal of Tax Law, 2013)
The Administrative Procedures Act prescribes procedural requirements that govern the rulemaking activities of administrative agencies, including the Internal Revenue Service. It imposes, inter alia, notice and comment requirements which an agency may only bypass for good cause. While the Treasury Department’s assertion of the good cause exception when promulgating regulations to prevent tax abuse is a plausible application of the exception, it is distinguishable from typical assertions of good cause in one critical respect. Unlike many other agencies claiming good cause to bypass the notice and comment procedure, the Internal Revenue Service’s organic statute provides a viable alternative by allowing for the retroactive application of regulations issued to prevent abuse. As a result, two functionally equivalent approaches to combat tax abuse emerge, differentiated only by the presence or absence of public participation in rulemaking processes. By comparing the public policy ramifications of these different rulemaking approaches, I contribute to key policy debates centering on administrative rulemaking procedures. I find that issuing regulations under the good cause exception provides efficiency gains, but does so at the expense of increased litigation risk and a failure to mitigate the principal-agent problem animating the rulemaking requirements in the Administrative Procedures Act. On the other hand, regulations issued retroactively reduce agency costs, provide modest efficiency gains and partially outsource the burden of compliance to interested constituents who participate in rulemaking processes. On these grounds, I conclude that Treasury’s assertion of good cause to promulgate regulations to prevent abuse is unconvincing given the viable alternative of retroactive application of finalized regulations. These conclusions are specific to the trade-offs inherent when Treasury promulgates regulations to prevent tax abuse, but also speak to IRS compliance with the Administrative Procedures Act more generally.